Eating disorders in patients with obsessive-compulsive disorder: Prevalence and clinical correlates - Sallet, Paulo C.; Alvarenga, Pedro Gomes de; Ferrão, Ygor; Mathis, Maria Alice de; Torres, Albina Rodrigues [UNESP]; Marques, Andrea; Hounie, Ana G.; Fossaluza, Victor; Rosario, Maria Conceição do; Fontenelle, Leonardo F.; Petribu, Katia; Fleitlich-Bilyk, Bacy (Wiley, 2010)
Objective: The objective is to evaluate the prevalence and associated clinical characteristics of eating disorders (ED) in patients with obsessive-compulsive disorder (OCD). Method: This is a cross-sectional study comparing 815 patients with OCD. Participants were assessed with structured interviews and scales: SCID-I, Y-BOCS, (Int J Eat Disord 2010; 43:315-325) Dimensional Y-BOCS, BABS, Beck Depression and Anxiety Inventories. Results: Ninety-two patients (11.3%) presented the following EDs: binge-eating disorders [= 59 (7.2%)], bulimia nervosa [= 16 (2.0%)], or anorexia nervosa [= 17 (2.1%)]. Compared to OCD patients without ED (OCD-Non-ED), OCD-ED patients were more likely to be women with previous psychiatric treatment. Mean total scores in Y-BOCS, Dimensional Y-BOCS, and BABS were similar within groups. However, OCD-ED patients showed higher lifetime prevalence of comorbid conditions, higher anxiety and depression scores, and higher frequency of suicide attempts than did the OCD-Non-ED group. Primarily diagnosed OCD patients with comorbid ED may be associated with higher clinical severity. Discussion: Future longitudinal studies should investigate dimensional correlations between OCD and ED. © 2009 Wiley Periodicals, Inc.
Keywords: Anorexia nervosa; Binge-eating disorder; Bulimia nervosa; Comorbidity; Eating disorders; Obsessive-compulsive disorder; Obsessive-compulsive spectrum; anorexia nervosa; anxiety disorder; binge eating disorder; bulimia; clinical assessment; clinical feature; comorbidity; controlled study; depression; disease association; disease severity; female; human; major clinical study; male; obsessive compulsive disorder; onset age; prevalence; priority journal; psychiatric treatment; suicide attempt; Adult; Anorexia Nervosa; Binge-Eating Disorder; Body Mass Index; Brazil; Bulimia Nervosa; Cross-Sectional Studies; Female; Humans; Male; Obsessive-Compulsive Disorder; Personality Inventory; Psychometrics